Loss of extra-striatal phosphodiesterase 10A expression in early premanifest Huntington's disease gene carriers - Wilson, Heather; Niccolini, Flavia; Haider, Salman; Marques, Tiago Reis; Pagano, Gennaro; Coello, Christopher; Natesan, Sridhar; Kapur, Shitij; Rabiner, Eugenii A.; Gunn, Roger N.; Tabrizi, Sarah J.; Politis, Marios (Journal of the neurological sciences, 2016)
Huntington's disease (HD) is a monogenic neurodegenerative disorder with an underlying pathology involving the toxic effect of mutant huntingtin protein primarily in striatal and cortical neurons. Phosphodiesterase 10A (PDE10A) regulates intracellular signalling cascades, thus having a key role in promoting neuronal survival. Using positron emission tomography (PET) with [11C]IMA107, we investigated the in vivo extra-striatal expression of PDE10A in 12 early premanifest HD gene carriers. Image processing and kinetic modelling was performed using MIAKAT™. Parametric images of [11C]IMA107 non-displaceable binding potential (BPND) were generated from the dynamic [11C]IMA107 scans using the simplified reference tissue model with the cerebellum as the reference tissue for nonspecific binding. We set a threshold criterion for meaningful quantification of [11C]IMA107 BPND at 0.30 in healthy control data; regions meeting this criterion were designated as regions of interest (ROIs). MRI-based volumetric analysis showed no atrophy in ROIs. We found significant differences in mean ROIs [11C]IMA107 BPND between HD gene carriers and healthy controls. HD gene carriers had significant loss of PDE10A within the insular cortex and occipital fusiform gyrus compared to healthy controls. Insula and occipital fusiform gyrus are important brain areas for the regulation of cognitive and limbic function that is impaired in HD. Our findings suggest that dysregulation of PDE10A-mediated intracellular signalling could be an early phenomenon in the course of HD with relevance also for extra-striatal brain areas. •Extra-striatal PDE10A expression is detectable by [11C]IMA107 PET imaging.•We studied extra-striatal PDE10A in early premanifest HD gene carriers.•First in vivo evidence for PDE10A loss in the insula and occipital fusiform gyrus.•Altered PDE10A could underlie cognitive and behavioural symptoms in HD.•Supports the role of PDEs in neurodegenerative disorders.